2010
DOI: 10.3389/fpsyg.2010.00236
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Changes along a Continuum of Speech Intonation is Impaired in Congenital Amusia

Abstract: A small number of individuals have severe musical problems that have neuro-genetic underpinnings. This musical disorder is termed “congenital amusia,” an umbrella term for lifelong musical disabilities that cannot be attributed to deafness, lack of exposure, or brain damage after birth. Amusics seem to lack the ability to detect fine pitch differences in tone sequences. However, differences between statements and questions, which vary in final pitch, are well perceived by most congenital amusic individuals. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
46
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 22 publications
3
46
2
Order By: Relevance
“…This outcome differs from the first reports on congenital amusia indicating unimpaired pitch processing in language material Patel et al, 2005), but is in agreement with more recent reports revealing pitch deficits also for language materials (Patel et al, 2008;Nguyen et al, 2009;Hutchins et al, 2010;Liu et al, 2010;Nan et al, 2010;Tillmann et al, 2011). The affected pitch processing in language material suggests a domain-general pitch deficit that is causing amusia.…”
Section: Discussioncontrasting
confidence: 71%
“…This outcome differs from the first reports on congenital amusia indicating unimpaired pitch processing in language material Patel et al, 2005), but is in agreement with more recent reports revealing pitch deficits also for language materials (Patel et al, 2008;Nguyen et al, 2009;Hutchins et al, 2010;Liu et al, 2010;Nan et al, 2010;Tillmann et al, 2011). The affected pitch processing in language material suggests a domain-general pitch deficit that is causing amusia.…”
Section: Discussioncontrasting
confidence: 71%
“…Other investigations have reported that amusic individuals have elevated thresholds for pitch-change detection and pitch-direction discrimination (34) along with impaired sensitivity to subtle pitch changes derived from speech stimuli (39,(42)(43)(44)(45)49). For example, individuals with amusia who speak a tone language have reduced ability to discriminate individual words that differ only in tone, and reduced sensitivity to pitch sequences derived from questions and statements (34).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the impairment underlying congenital amusia may be highly relevant to music because of the reliance of music on finegrained pitch movements. Supporting this hypothesis, a recent investigation revealed that amusic individuals can correctly identify unambiguous examples of questions and statements, but exhibit deficits with subtle exemplars (49).…”
mentioning
confidence: 93%
“…In other words, the amusic deficit has been proposed to lie in the acoustic analysis of sounds, and since music processing lies downstream from acoustic processing and makes high demands on fine-grained pitch resolution, amusics manifest a musical impairment. The literature has since been converging towards the finding that amusics display significantly worse pitch discrimination performance as compared to controls (e.g., Hutchins, Gosselin, & Peretz, 2010;Jiang, Hamm, Lim, Kirk, & Yang, 2010;Liu, Patel, Fourcin, & Stewart, 2010;Jiang et al, 2012;Liu et al, 2013;Nan, Sun, & Peretz, 2010;Omigie & Stewart, 2011;Patel, Wong, Foxton, Lochy, & Peretz, 2008;Tillmann, Burnham, et al, 2011;Tillmann, Rusconi, et al, 2011), bearing out Peretz et al's (2002) hypothesis. Indeed, in addition to poor performance on the MBEA, a pitch discrimination deficit has become a diagnostic benchmark for the identification of new amusic cases.…”
mentioning
confidence: 90%
“…For instance, amusics seem to perceive speech normally, and they can recognize and sing songs through lyrics but not the tune (Ayotte, Peretz, & Hyde, 2002;Dalla Bella, Gigu ere, & Peretz, 2009; TremblayChampoux, Dalla Bella, Phillips-Silver, Lebrun, & Peretz, 2010). However, amusics do show an impairment of pitch perception in speech (Hutchins, Gosselin, et al, 2010;Hutchins, Zarate, Zatorre, & Peretz, 2010;Liu et al, 2010;Patel et al, 2008;Tillmann, Rusconi, et al, 2011), but as Peretz (2013) notes, this deficit is mild relative to their impairment with musical materials. Assuming modular Fig.…”
mentioning
confidence: 94%